The Impact Of Technological Advancements In Radiology And Ultrasound Equipment And Banking Innovation On Improving The Efficiency Of Healthcare Investment : A Proposed Analytical Framework For Applied And Financial Sciences - Suad Hashim Rahi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Healthcare systems increasingly require alignment between technological modernization and financial mechanisms to support sustainable investment management. Specific Background: This study examines technological advancements in radiology and ultrasound equipment together with banking innovation as complementary dimensions within Iraqi healthcare institutions. Knowledge Gap: Previous studies addressed technological development and financial innovation separately, while analytical models integrating both applied medical and financial perspectives remain limited. Aims: The research aims to construct and empirically test an analytical framework explaining the relationship between medical technology development, banking innovation, and healthcare investment efficiency. Results: Using a descriptive-analytical approach based on literature review and questionnaire data from 103 healthcare and banking employees analyzed through SPSS and Excel, the findings reveal statistically significant positive relationships among variables, with technological development showing the strongest regression coefficient (β = 0.52) followed by banking innovation (β = 0.39). The combined model explains 64% of the variance in healthcare investment efficiency (R² = 0.64). Novelty: The study introduces an integrated analytical framework linking diagnostic technology modernization with innovative financing mechanisms within a unified applied and financial sciences perspective. Implications: The findings support coordinated technological modernization programs, flexible financing policies, and expanded financial technology adoption to support sustainable healthcare investment and improved resource management in developing healthcare systems. Highlights: Statistical Model Accounted for 64% Variance in Investment Performance Outcomes. Diagnostic Equipment Modernization Showed the Highest Regression Contribution. Survey Responses Demonstrated Strong Cross-Sector Awareness of Technology–Finance Alignment. Keywords: Medical Technology, Banking Innovation, Healthcare Investment Efficiency, Radiology Equipment, Financial Integration